FAKTOR YANG MEMPENGARUHI SISA MAKANAN DAN BIAYA YANG TERBUANG PADA PASIEN SKIZOFRENIA RAWAT INAP - Astri Fitriati; Reni Sofiyatin; Suhaema Suhaema; Luh Suranadi (Jurnal Gizi Prima (Prime Nutrition Journal), 2021)
Background : The success of a food maintenance system can be evaluated by observation of food waste that causes the cost to be wasted and will have an impact on the anggran used for the procurement of foodstuffs.  The observations showed that in Mutiara Sukma Mental Hospital, there were still food waste that was not consumed by patients.Objective : This study aims to analyze "factors that affect food waste and its relationship to the cost of food waste".Method : The type of research is cross sectional with survey approach. Respondents to this study were 24 patients who underwent hospitalization from December 1 to 10, 2020. The food waste data was taken by observation using Comstock's visual method and compared with the price of the menu, patient assessment data on food taste was obtained by interview using questionnaires. The relationship between food waste and food waste costs was obtained by pearson correlation tests.Result : Average food waste in period 1 menu cycle of 9.07%, from the results of double logistic regeresi test there is no relation between food waste wit ofh age, gender and taste of food. The cost of food waste cost per patient per day is Rp. 2283.5,-Conclusion : Food waste correlated with the cost of food waste. Latar belakang : Keberhasilan suatu sitem penyelenggaraan makanan dapat dievaluasi dengan pengamatan sisa makanan yang menyebabkan adanya biaya yang terbuang secara sia-sia dan akan berdampak terhadap anggaran yang digunakan untuk pengadaan bahan makanan.  Hasil observasi menunjukkan bahwa di Rumah Sakit Jiwa Mutiara Sukma masih ditemukan adanya sisa makanan yang tidk dikonsumsi oleh pasien.Tujuan : Penelitian ini bertujuan untuk menganalisis       “ Faktor-faktor yang mempengaruhi sisa makanan dan hubungannnya dengan biaya sisa makanan”.Metode : Jenis penelitian adalah cross sectional. Responden sebanyak  24 pasien yang menjalani rawat inap di ruang pemulihan. Waktu penelitian 1-10 Desember  2020. Metode visual Comstock untuk pengukuran sisa makanan kemudian melihat biaya dari sisa dengan membandingkan dengan harga menu persajian. Analisis faktor yang mempengaruhi sisa dengan uji regresi logistk ganda dan melihat hubungan antara sisa makanan dan biaya sisa makanan diperoleh dengan uji korelasi pearson.Hasil : Rata-rata sisa makanan dalam periode 1 siklus menu sebesar 9.07%, tidak terdapat hubungan antara sisa makanan dengan umur, jenis kelamin  dan cita rasa makanan. Biaya sisa makanan per pasien perhari sebesar Rp. 2283.5.Kesimpulan : Sisa makanan berkorelasi dengan biaya sisa makanan.